2021
DOI: 10.1108/jfm-07-2021-0073
|View full text |Cite
|
Sign up to set email alerts
|

The indirect effect of high-performance work practices on employees’ performance through trust in management

Abstract: Purpose The construction industry activities play a key role in achieving socio-economic development and sustaining economic growth in many countries. Increased awareness about the role of human resource management in employee performance has led construction firms to evaluate and focus on high-performance work practices (HPWPs) components, which intend to cultivate employee and organizational performance. This study aims to explain HPWPs affect employee performances through the mediating influence of trust in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 106 publications
0
9
0
1
Order By: Relevance
“…Affective commitment is defined as a strong intention of the people in organisations to maintain their membership at their current workplace for long-term goals (Allen & Meyer, 1990). Furthermore, the workers will proactively give their best for organisations and they have a strong will to show their creativity and share innovative ideas to assist their companies (Jalali et al, 2021). Raveendran and Gamage (2019) found a strong link between affective and performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Affective commitment is defined as a strong intention of the people in organisations to maintain their membership at their current workplace for long-term goals (Allen & Meyer, 1990). Furthermore, the workers will proactively give their best for organisations and they have a strong will to show their creativity and share innovative ideas to assist their companies (Jalali et al, 2021). Raveendran and Gamage (2019) found a strong link between affective and performance.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, SMEs need to have continuous innovation that requires creativity and innovative behaviour from people within organisations, leading to creativity and innovative behaviour from people within organisations, leading to better SME performance (Lei et al, 2019). Further, SME innovative performance will lead the consumers to the repurchase intention (Alhabsy, 2021).Scholars believe that trust will support this mission by enhancing SMEs' innovation performance in the context of Indonesia during pandemic crises (Jalali et al, 2021;Pratono, 2021). Newly, Seepana et al (2021 found that innovation performance is influenced by trust among workers, indicating confidence and willingness to engage in a strong relationship with another person within SME sectors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini merupakan hasil daripada bentuk peran strategis sumber daya manusia dibutuhkan dalam upaya pencapaian tujuan dari visi organisasi (Al-Ayed, 2019;Collins, 2021). Pegawai yang melaksanakan kinerjanya secara baik hasilnya dapat memberikan efek positif dalam mempengaruhi prestasi kerja organisasi sehingga akan memicu pencapaian tujuan organisasi yang telah ditetapkan (Arthur et al, 2021;Jalali et al, 2021;Joseph Tawk, 2021) Salah satu Elemen utama yang dapat memberikan efek signifikansi kinerja pegawai adalah spesifikasi pekerjaan (Riggio, 2021;S. Robbins & Judge, 2009;Tabara, 2018).…”
Section: Pendahuluanunclassified
“…The beginning of the 21st century drew the attention of HPWP researchers (Jewell et al, 2022). Numerous studies in the existing literature indicate how HPWPs improve organizational performance (Jalali et al, 2021). Yet, few studies have addressed the positive association between HPWPs and job outcomes (Zhiqiang et al, 2021), and the underlying intervening mechanisms in the HPWPs and job performance relationship are seldom investigated (Abboh et al, 2022).…”
Section: Introductionmentioning
confidence: 99%